The study of the political economy of the media in the twenty-first century. (1st September 2014) - Wasko, Janet
This discussion presents a brief overview of the establishment and expansion of the study of the political economy of media and communications, followed by attention to some of current directions of this approach. Themes and concepts developed by political economists of the media are reviewed, as well as internal and external critiques of the approach. Recent developments are discussed, including the growth of integrated studies, the return to classic Marxist themes, integration of digital technologies, and attention to policy and activism.